Neoconservative criticism : Norman Podhoretz, Kenneth S. Lynn, and Joseph Epstein - Winchell, Mark Royden, 1948- (Boston : Twayne Publishers, 1991)
Examines the cultural ramifications of neoconservatism by analyzing the main features of these commentators' thoughts and writings.
Includes bibliographical references (p. 161-169) and index.
Young Adult.
Young Adult
Keywords: Epstein, Joseph, -- 1937-; Lynn, Kenneth Schuyler; Podhoretz, Norman; Epstein, Joseph, -- 1937-; Lynn, Kenneth Schuyler; Podhoretz, Norman; American literature -- History and criticism -- Theory, etc; Conservatism and literature -- History -- 20th century; Criticism -- United States -- History -- 20th century; American literature -- History and criticism; Conservatism and literature -- History; Criticism -- History